Tinjauan Yuridis Terhadap Kedudukan Rumah Tahanan Negara Sebagai Tempat Penyanderaan Bagi Penanggung Pajak - Yadhy Cahyady (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Taking the tax bearer hostage is one of the actions in the context of tax collection with the aim of getting the tax bearer to pay off the tax debt and tax collection costs. Hostage actions against tax bearers are carried out very selectively, carefully, and are a last resort. The aim of this research is to analyze the concept of a hostage location for tax payers. The research method used is normative legal research with a statutory approach. The data used is secondary data obtained from legal materials in the form of statutory regulations and reference books. From the research conducted, it is known that the Ministry of Finance has the responsibility to establish a hostage location for taxpayers. Before the hostage location was set up by the Ministry of Finance, taxpayers who were held hostage were kept in state detention centers and separated from other detainees.